Caracterização de membranas de poliamida 66 preparadas pelo método de inversão de fases - Poletto, Patrícia (My University, 2014)
In the present study, polyamide 66 (PA 66) membranes were prepared by phase inversion (PI) and characterized in order to verify their potential application in separation processes. PA 66 membranes were prepared using two different solvents, formic acid (FA) and chloridric acid (HCl), and water as a non-solvent. Membranes prepared in film form (not supported) were characterized by Fourier-transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC) and the results showed that the chemical structure and thermal behavior of the PA 66 were not altered by the use of acids as solvents. The films revealed an asymmetric structure with a dense top layer and a porous sublayer featuring spherical pores observed by scanning electron microscopy (SEM). The thickness of the dense layer varied from 10 to 25 μm in films prepared with FA and HCl, respectively. The increase in thickness of the dense layer, i.e., the reduction of empty spaces, directly influenced the results regarding water absorption percentage and total porosity. The porosity found was 15% and 50% for films prepared with FA and HCl, respectively. Water vapor flux was lower in films with a thicker dense layer as a result of a greater resistance to mass transfer. In order to increase mechanical resistance in polyamide films, supported membranes with polyester fabric were prepared for latter application in separation processes through high pressure. Supported membranes were characterized by BET techniques for the determination of pore size, reverse osmosis and ultrafiltration assays. Both membranes prepared with FA and HCl showed very similar pore sizes when analyzed by/with BET. A compression assay with pure water performed at a pressure of 40 bar revealed that membranes prepared with FA undergo greater compaction of its structure and had a permeate flux value of approximately 22 Lm-2h-1 whereas the membrane prepared with HCl had a permeate flux value of 312 Lm-2h-1. On reverse osmosis assays, the maximum rejection to sodium chloride was 7% and 4% for FA-3 and HCl-3 membranes, respectively. On ultrafiltration assays, performed at 15 bar, both membranes had rejection values close to 70% for egg albumin and 80% for bovine albumin. Based on this result, it is possible to conclude that both membranes revealed pore size and rejection characteristics for application in ultrafiltration processes.
Neste trabalho foram preparadas membranas de poliamida 66 (PA 66) pelo método de inversão de fases (IF) e caracterizadas com o objetivo de verificar sua possível aplicação em processos de separação. As membranas de PA 66 foram preparadas utilizando dois solventes diferentes, ácido fórmico (AF) e ácido clorídrico (HCl) e água como não-solvente. As membranas preparadas na forma de filmes (não suportadas) foram caracterizadas por Espectroscopia de Infravermelho com Transformada de Fourier (FT-IR) e calorimetria exploratória diferencial (DSC), onde os resultados mostraram que a estrutura química e o comportamento térmico da PA 66 não foram alterados como o uso de ácidos como solventes. Os filmes apresentaram estrutura assimétrica, com formação de camada densa na parte superior seguida de subestrutura de poros esféricos observada por microscopia eletrônica de varredura (MEV). A espessura de camada densa variou de 10 à 25 μm, para o filme preparado em AF e HCl, respectivamente. O aumento da espessura da camada densa, ou seja, a redução de espaços vazios influenciou diretamente os resultados de percentual de água absorvida e porosidade total. A porosidade foi de 15 contra 50% para os filmes preparados em AF e HCl, respectivamente. O fluxo de vapor de água foi menor para os filmes com maior espessura de camada densa, devido ao aumento da resistência ao transporte de massa. Com o objetivo de aumentar a resistência mecânica dos filmes de poliamida, foram preparadas membranas suportadas em tecido de poliéster para posterior aplicação em processos de separação que utilizam altas pressões. As membranas suportadas foram caracterizadas pelas técnicas de BET para determinação de tamanho médio de poros, ensaios de osmose inversa (OI) e ultrafiltração (UF). Ambas as membranas preparadas em AF e HCl apresentaram valores de tamanho de poro muito próximos quando analisado por BET. O ensaio de compactação com água pura realizado a 40 bar de pressão revelou que as membranas preparadas em AF sofrem maior compactação na sua estrutura apresentando fluxo de permeado em torno de 22 Lm-2h-1 enquanto a membrana preparada em HCl apresentou fluxo de 312 Lm-2h-1. No ensaio de OI, a rejeição máxima ao cloreto de sódio foi de 7% e 4% para a membrana AF-3 e HCl-3, respectivamente. Nos ensaios de ultrafiltração (UF), realizados a 15 bar, ambas as membranas apresentaram valores de rejeição próximos a 70% para albumina de ovo e 80% para albumina bovina. Com esse resultado, podemos concluir que ambas as membranas apresentaram características de tamanho de poro e rejeição para aplicações em processos de UF.
Keywords: Engenharia de materiais e metalúrgica; Membranas (Tecnologia); Membranas filtrantes; Separação (Tecnologia); Membranes (Technology); Membrane filters; Separation (Technology)